Perception of Food Hazards – Exploring the Interaction of Gender and Experience in an Experimental Study - Böcker, Andreas; Justus Liebig University Giessen (My University, 2002)
This paper aims to analyse whether interaction effects between gender and experience have an impact on food-related risk perception. While both components have received considerable attention in the risk research literature, possible interaction effects between them have rarely been considered yet. For data generation the psychometric approach was applied. Participants in an experiment rated selected food hazards with regard to 18 risk characteristics. Responses are grouped in four sub-samples, according to gender and foodpoisoning experience. In a first step, principle-component analysis reduces these ratings to two dimensions. Plotting hazard perceptions for each sub-sample in a perceptual map then allows to identify differences between the sub-samples. Finally, significant differences between sub–samples are identified with analyses of variance for single risk characteristics. The results suggest that experience does not affect risk perception directly but through interacting with gender. This effect is not marginal and partially coexists with a pure gender effect and partially is the only significant effect.
Keywords: ddc:330; ddc:630